Persepsi Siswa Vokasi terhadap Perencanaan, Pelaksanaan dan Evaluasi Pembelajaran Kerja Bengkel dan Gambar Teknik - Sonia Dora; Hansi Efendi (Jurnal Pendidikan Teknik Elektro, 2023)
Based on the observations made, the learning process at SMK Negeri 1 Ranah Batahan is not in accordance with the subjects and student characteristics. Often student learning outcomes do not meet the minimum standard of completeness for practicum subjects and technical drawing. Many teachers, including vocational teachers, complain of difficulties in implementing the 2013 curriculum. The learning process needs to be updated so that students do not only receive information from their teachers, but also actively participate in finding information, data, and the knowledge they want to learn. For this reason, the teacher as a facilitator and motivator to optimize student learning should choose the right strategy to increase students' willingness to learn. For this reason, it is necessary to look at student responses regarding the planning, implementation and evaluation of workshop work subjects and technical drawings at SMKN 1 Ranah Batahan. Based on the results of the study, it was concluded that the students' opinions on planning, implementation of learning for Workshop Work Subjects and Technical Drawings of Class X Audio Video Engineering Skills Packages at SMK N 1 Ranah Batahan described the respondent's achievement level of 86.30% in the good category. As well as students' responses to the Evaluation of Subjects for Workshop Work and Technical Drawing Subjects with the respondent's achievement level of 87.11% in the good category.